Optimalisasi Pemanfaatan Taman Kuliner Tunggal Sangomang Bagi Pemberdayaan Pedagang Kreatif Lapangan Di Kota Palangka Raya - Masrukin Masrukin; Ananto Sarkoro (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
Creative merchants of the field or street vendors hereinafter referred to as PKL are traders who in the business use the facilities and equipment that are easily disassembled, transferred or use a place of business that occupies the land Local Government or other parties. Because of the phenomena that arise in implementing the relocation program of the creative trader's field that is done by the city government, so it is created this research aimed to know and describe how the optimization The utilization of the single culinary Park Sangomang for empowering creative traders field in Palangka Raya city. This research uses qualitative research methods. The technique of determining the informant in this research is the technique of purposive sampling so that the informant in this research is involved in the implementation of optimization of a single culinary park for the empowerment of field creative traders Is the head of the setup and aesthetics of the city of Palangkaraya, and creative traders field a single culinary park Sangomang. Data is collected through observation methods, interviews, and documentation. And the data is analyzed by way of data reduction, data presentation, and withdrawal of conclusions. Based on the results of this study, it can be known that: 1) the empowerment of creative traders in the field of single Culinary park Sangomang in the city of Palangkaraya is good enough. 2) The process of the Creative Trader Relocation field to a single culinary park Sangomang is good enough. 3) The constraints of the creative trader's field in a single culinary park Sangomang is not maximal utilization of facilities and infrastructures that support the security and convenience of creative traders field and also visitors a single culinary park Sangomang.